(untitled) (AYUSHDHARA, 2017)
Mutraghata is a group of Obstructive Uropathy disorders which has been dealt in detail in almost all ancient treatises, in which the Mutragranthi, Mutrasanga, Bastikundalika & Mutrastheela are the conditions which are similar to the BPH in respective of obstructive as well as irritative phases. Benign prostatic hyperplasia (BPH) is a common cause of male lower urinary tract symptoms (LUTS). BPH is a senile disorder and chiefly affects individuals above the age of 40 years. The symptoms are increased frequency of micturition, dribbling, hesitancy, and the features of chronic urinary retention. The symptoms of benign prostatic hyperplasia (BPH) closely resemble both in anatomically and symptomatically with Vatastheela which is mentioned in Ayurvedic text. Surgical management has been accepted as the standard management but is associated with many disadvantages as well as complications, which may not be acceptable at this age. Conservative management with modern medicines is also not free from side effects. So, in this age-group, there is a need for much safer alternative method of management. Mustadi kalpacited by Acharya Sushruta in the context of Mutraghat chikitsa is a well known therapeutic drug in this context. A study was carried out to evaluate its efficacy in which 30 patients were selected for the trail with the symptoms of BPH and were subjected to administration of Mustadi kalpa in the dose of 10 mg TDS in divided doses orally for 45 days. The Total effect of the formulation has provided considerably significant relief on the subjective as well as objective parameters. Mustadi kalpa was found safe and effective in symptomatic management of Mootraghata (BPH) by virtue of its Shothhara, Balya, Tridoshhara and Vatanuloman properties.